Willingness to pay by using travel cost method in Chitwan National Park, Nepal - Aryal, M.; Dutta, J. P.; Regmi, P. P.; Pandey, K. R. (Journal of the Institute of Agriculture and Animal Science, 2018)
This study assessed the impact of tourism and willingness to pay by foreigners in Chitwan National Park of Chitwan district during the year 2007-2008. Eighty tourists were selected randomly to evaluate the recreational value of Chitwan National Park to protect the biodiversity of buffer zone area in Chitwan National Park. The tourism created the local employment opportunities to local people but it was unplanned and location specific. Since the program has focused in both community development and conservation awareness activities however, the study showed that only public infrastructure development was emphasized instead of sensitizing the members towards the conservation issues of protected areas. The study examined how much Park visitors were willing to pay to visit the Park. Annual benefits from the Park were considerable - the total annual consumer surplus obtained from recreation in the Park was approximately USD 233 million. Various factors influence the visitors like travel cost, household income, and the quality of the Park. Improvements in quality of the Park were likely to increase recreational benefits. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page :1-10